Polyclonal antibodies to detect the cp-rt protein of potato mop-top virus / anticuerpos policlonales para la detección de la proteína cp-rt del potato mop-top virus (2012)
Potato mop-top virus (PMTV) causes an important re-emerging disease in potato crops in Colombia due to the increased incidence of its protozoan vector Spongospora subterranea f.sp. subterranea (Sss), the causing agent of Powdery scab disease. For an accurate detection of PMTV it is recommended to combine different diagnostic tests and evaluate multiple samples per plant or tissue. In order to increase the number of available tools for detection of PMTV, antibodies targeting the RT domain of the CP-RT protein were developed in this work. Sequencing of the RT domain from the colombian strain R25 was achieved and using bioinformatic analysis, a potential antigenic region was identified. A peptide mimicking the antigenic region was inoculated in rabbits for the production of polyclonal antibodies. The antibodies were tested by ELISA using Nicotiana benthamiana bait-plants infected with Sss cystosori and potato plants collected in La Unión (Antioquia). The validity of serological tests was confirmed by RT-PCR. A complete sequence of the RT domain and 441 nt of the CP gene were obtained. Phylogenetic analysis identified strain R25 as closely associated to the PMTV lineage distributed worldwide. A total of 19.26 mg of anti-CP-RT polyclonal antibodies useful in detecting PMTV in infected plants were obtained. As CP-RT is involved in transmission of PMTV by Sss, these antibodies will be useful for supporting not only diagnostic programs but also basic and epidemiologic studies aimed at understanding interactions between PMTV and Sss. / El Potato mop-top virus (PMTV) es uno de los virus re-emergentes en los cultivos de papa de Colombia, como resultado del aumento de la incidencia de su vector natural, el protozoo Spongospora subterranea f.sp. subterranea (Sss), agente causal de la Sarna polvosa de la papa. Para la detección del virus se recomienda la realización simultánea de diferentes pruebas, así como la evaluación de múltiples submuestras por tejido bajo análisis. Con el fin de ampliar el rango de herramientas para la detección de PMTV, se obtuvieron anticuerpos dirigidos al dominio RT de la proteína CP-RT. Se secuenció dicho dominio en el aislamiento colombiano R25 de PMTV y se realizaron análisis bioinformáticos para ubicar regiones peptídicas con alto potencial inmunogénico. El péptido seleccionado fue inoculado en conejos para obtener anticuerpos, cuya utilidad fue evaluada a partir de pruebas de ELISA indirecto en plantas señuelo de Nicotiana benthamiana inoculadas con quistosoros de Sss y en plantas de papa obtenidas en La Unión (Antioquia). Estas pruebas estuvieron acompañadas con evaluaciones de RTPCR. Se obtuvo la totalidad del dominio RT, así como 441 nt del gen CP. Los análisis filogenéticos identificaron la cepa R25 como asociada al linaje de PMTV mundialmente distribuido. Se obtuvieron 19,26 mg de anticuerpos, los que resultaron efectivos para detectar PMTV. Ya que CP-RT es responsable de la transmisión del PMTV por Sss, estos anticuerpos permitirán no sólo apoyar los programas de diagnóstico, sino también estudios básicos y epidemiológicos tendientes a evaluar las interacciones del PMTV y Sss.